Pengaruh Net Profit Margin, Return On Asset, Return On Equity, dan Earning Per Share Terhadap Harga Saham di Masa Pandemi Covid-19 (Studi Empiris Pada Perusahaan Publik Sektor Pertambangan di Bursa Efek Indonesia) - Nafis Dwi Kartiko; Ismi Fathia Rachmi (Jurnal Riset Bisnis dan Investasi, 2021)
The COVID-19 pandemic has caused disruptions in demand and sales of mining materials. The aftermath of the event affected world mining production. This will certainly affect the Share Price of mining sector companies on the Indonesia Stock Exchange (IDX). This study aims to determine the influence of Net Profit Margin (NPM), Return On Asset (ROA), Return On Equity (ROE), and Earning Per Share (EPS) on Share Prices. The population in this study is mining sector companies registered in IDX period 2020 as many as 49 companies. The data collected comes from the interim financial report data published by IDX every month from March 2020 to December 2020. The analysis method used is multiple linear regression analysis with the help of SPSS 23 software. The results showed that NPM, ROA, ROE, and EPS had a significant impact on the share price.